Students’ Attitudes Towards the Teaching of Speaking by Native-English-Speaking Teachers: A Survey Research at Thai Binh Teacher Training College - Do, Thi Minh Nguyet (University of Languages and International Studies, 2017)
This study investigated students’ attitudes towards the teaching of speaking by native-English-speaking teachers. Participants were 100 English majors at Department of Foreign Languages, Thai Binh Teacher Training College, where the researcher works as a n (...)